Converging focal radiation and immunotherapy in a preclinical model of triple negative breast cancer: contribution of VISTA blockade - Pilones, Karsten A; Hensler, Michal; Daviaud, Camille; Kraynak, Jeffrey; Fucikova, Jitka; Galluzzi, Lorenzo; Demaria, Sandra; Formenti, Silvia C (Oncoimmunology, 2020)
Antibodies targeting the co-inhibitory receptor programmed cell death 1 (PDCD1, best known as PD-1) or its main ligand CD274 (best known as PD-L1) have shown some activity in patients with metastatic triple-negative breast cancer (TNBC), especially in a recent Phase III clinical trial combining PD-L1 blockade with taxane-based chemotherapy. Despite these encouraging findings, however, most patients with TNBC fail to derive significant benefits from PD-L1 blockade, calling for the identification of novel therapeutic approaches. Here, we used the 4T1 murine mammary cancer model of metastatic and immune-resistant TNBC to test whether focal radiation therapy (RT), a powerful inducer of immunogenic cell death, in combination with various immunotherapeutic strategies can overcome resistance to immune checkpoint blockade. Our results suggest that focal RT enhances the therapeutic effects of PD-1 blockade against primary 4T1 tumors and their metastases. Similarly, the efficacy of an antibody specific for V-set immunoregulatory receptor (VSIR, another co-inhibitory receptor best known as VISTA) was enhanced by focal RT. Administration of cyclophosphamide plus RT and dual PD-1/VISTA blockade had superior therapeutic effects, which were associated with activation of tumor-infiltrating CD8+ T cells and depletion of intratumoral granulocytic myeloid-derived suppressor cells (MDSCs). Overall, these results demonstrate that RT can sensitize immunorefractory tumors to VISTA or PD-1 blockade, that this effect is enhanced by the addition of cyclophosphamide and suggest that a multipronged immunotherapeutic approach may also be required to increase the incidence of durable responses in patients with TNBC.
Keywords: myeloidní supresorové buňky; cyclophosphamide; Animals; immunosurveillance; CD8-Positive T-Lymphocytes; focal radiotherapy; immunological checkpoints; Humans; Mice; MDSCs; triple-negativní karcinom prsu; 4T1 cells; Triple Negative Breast Neoplasms; myeloid cells; CD8-pozitivní T-lymfocyty; imunoterapie; zvířata; C10orf54; VSIR; CD8+ T cells; Immunotherapy; PD-1; TCGA; lidé; Myeloid-Derived Suppressor Cells; myši